Empirical Verification of the Existence and Functioning of Internal Controls in the Preparation of a Consolidated Property Balance Sheet for the State and Municipalities in Slovenia - Jasna Ida Zafred (Central European Public Administration Review)
The consolidation process, where a group of enterprises is presented as a single one, is prescribed by international accounting standards, and in accordance with them it has been taken over by Slovenian accounting standards and International Public Sector Accounting Standards. It may be conducted after prior preparation of basic financial statements of the controlling and the controlled enterprise. From the professional directives derives one of the demands that between consolidated standings there must not be any so-called "quasi-differences" due to unregulated accounting. In spite of the fact that Slovenian subjects of the public sector do not prepare financial statements in a way as determined by the standards, consolidation is being carried out, but for certain data of the balance sheets and based on a special regulation. This regulation allows the appearance of differences between the budgets users what influences the standing of the general state fund. In the research, by the method of random sampling by the use of an opinion poll according to the components of the COSO model, we empirically verified the effectiveness of the internal controlling system in the preparation of original documents of the balance sheets in the Slovenian public sector. We found out that formally differences are allowed, even quasi-differences, due to which reliability of a consolidation financial statement is questionable. Verification of the component of the controlling environment has shown for example that legal limitation periods for the confirmation of open positions are determined too early, and the proceedings are not agreed upon exactly enough when there is an imbalance between receivables and liabilities in the consolidation. In situations of short-term receivables and liabilities towards budget users in 31.12., there are standings that may lead to the risk of appearance of differences in the consolidation and for a string of accounts we found in the component of the controlling activity that budget users did not even the standings successfully or did not even balance the standings in 31.12., due to what differences appeared. This was the cause that measures were determined by accounting offices for the avoiding of an appearance of differences. The question of the component of information and communication was answered by accountants who wish they had more education, and the superiors who could use the information from financial statements better for their decision-making. Their software is still not safe enough, as in some cases the database of financial data is accessed. The results in the component of following showed that in several places audits of the procedure of preparation of property balance sheets were not performed.